Investing in Organization: Tips, Tools, and Benefits - Cobourn, Alston (My University, 2024)
Over the past year, East Carolina University’s University History and Records Department has been working smarter, not harder, through increased organization. On the whole, archives and records professionals are overworked, which can make even the task of staying organized overwhelming. This talk will share the ways our department has become better organized and the benefits that have yielded, including smoother transitions between projects, decreased stress in managing student workers, less confusion, and being able to meet more annual goals. I will discuss how we have used specific tools and modified procedures to become a more organized department. Attendees will leave the session energized with concrete ideas they could implement at their own institutions.
Keywords: Archives; Management